Corporate Stock and Bond Return Correlations and Dynamic Adjustments of Capital Structure. (31st March 2015) - Nieto, Belen; Rodriguez, Rosa
Abstract This paper analyses the effects of dynamic correlations between stock and bond returns issued by the same firm on the speed of adjustment towards target leverage. The results show that the estimated correlations are time varying, show persistence and differ among firms. Analysis of the potential explanatory variables reveals that the correlations decrease with negative expectations about future aggregate risks, but only for firms with a low default probability. In contrast, correlations are positively associated with specific risk measures, especially idiosyncratic stock risk and financial leverage. The positive relationship between the correlations and the leverage ratio suggests that target leverage can be achieved faster when the stock–bond correlation is high. Our results show that this is the case.